EXTREME VALUE ANALYSES AND JOINT DENSITIES OF METOCEAN LOADS FOR MALAYSIAN WATERS - MOHAMAD SELAMAT, IDZWAN (2014)
Environmental loads arising from wind speed, wave height and current are the major key design elements in offshore and coastal structures. These environmental loads also affect maritime operational activities. In the case of offshore platforms, the worst effect from the environmental loads is usually due to the wave force. In order to avoid offshore platforms from being subjected to extreme loadings, the design crest elevation should be above the extreme tides and storm surges. In this research, the extreme effect of wind and wave is studied as joint occurrences as opposed to the standard method of considering wind and wave as two independent loads acting on offshore structures simultaneously. The extreme wave height is determined from annual maxima and joint density distribution with wind. In the design of offshore platforms, wind and wave are designed as independent loads.